Pessoa com deficiência e teletrabalho : reflexões à luz do valor social do trabalho (inclusão social e fraternidade) - Bublitz, Michelle Dias (2014)
Mankind has reached the twenty-first century facing a globalized and computerized world. Social relations change rapidly in every field, from the family to work. Information technology and communication enables working relationships transcend indoors, allowing workers to perform their tasks from anywhere. Geographical barriers are quickly broken. New working relationships are necessary and teleworking presents itself as a reality and possibility of livelihood for any worker. Presents itself as a possibility of integrating people with disabilities into the labor market. However, it is observed, therefore, that teleworking as a result of technological innovation, allows you to see advantages and disadvantages. Regarding the advantages, one can cite as an example the reduction of transport costs, clothing, fuel and overall cost, rationalization of facilities, equipment and working materials, also suppressing the rigidity of time and freedom to meet in period of employment, personal interests and family incidental. Moreover, this way of working has the disadvantage of possible deterioration of working conditions, including isolation arising from the lack of contact with other workers. However, it is known that the work done in establishing the employer allows, in many roles, contact with colleagues, providing casual conversation, exchange of ideas and discussion of personal and family problems in an atmosphere of professional and emotional interaction. Right now, the revitalization of the principle of fraternity, rescued by the current Federal Constitution, means redefining the role of the state and the particular, to coordinate and promote multiple solidarities, public and private policies that foster social inclusion. The fraternity encouraging a new culture of unconditional respect for others, a paradigm that ensures equal effectiveness, enabling the dignity of the human person.